Moral Degradation, Business Ethics, and Corporate Social Responsibility in a Transitional Economy - Zheng, Q.; Luo, Yadong; Wang, S. (Springer Netherlands, 2014)
This article theoretically proposes and empirically verifies an understudied issue in the business ethics (BE) and corporate social responsibility (CSR) literature-how moral degradation (MD) in a society influences the relationship between BE or CSR and firm performance (i.e., corporate legitimacy and competitive advantage). Building on strategic choice theory, we propose that both BE and CSR become more important in enhancing business success when the perceived MD is heightened. Our analysis of 300 firms operating in China statistically confirms our hypotheses: first, under high MD, firms' engagement in CSR results in higher corporate legitimacy and competitive advantage, and second, their adherence to ethical business codes leads to higher corporate legitimacy. We conclude the article by outlining the implications for both theory and practice.